Mistaking the Map for the Territory: What Society Does With Medicine; Comment on "Medicalisation and Overdiagnosis: What Society Does to Medicine" - Alistair Wardrope (Kerman University of Medical Sciences, 2017)
Van Dijk et al describe how society's influence on medicine drives both medicalisation and overdiagnosis, and allege that a major political and ethical concern regarding our increasingly interpreting the world through a biomedical lens is that it serves to individualise and depoliticize social problems. I argue that for medicalisation to serve this purpose, it would have to exclude the possibility of also considering problems in other (social or political) terms; but to think that medical descriptions of the world seek to or are able to do this is to misunderstand the purpose and function of model construction in science in general, and medicine in particular. So, if medicalisation is nonetheless used for the depoliticization described by many critics, we must ask what society does with medicine to give it this exclusive authority. I propose that the problem arises from a tendency to mistake the map for the territory, and think a tool to understand certain aspects of the world gives us the complete picture. To resist this process, I suggest health workers should be more open about the purpose and limitations of medicalisation, and the value of alternative descriptions of different aspects of human experience.